GREEN ACCOUNTING AND CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE ON FIRM VALUE: EVIDENCE OF PROFITABILITY MEDIATION IN INDONESIAN ENERGY COMPANIES - Bambang Hermawan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the effect of Green Accounting and Corporate Social Responsibility Disclosure (CSRD) on firm value, with profitability as a mediating variable, in energy sector companies listed on the Indonesia Stock Exchange during the 2018-2023 period. This study employs a quantitative approach using a sample of 13 companies selected through purposive sampling, resulting in 78 observations. Data were analyzed using panel data regression with the Random Effect Model (REM), and mediation was tested using the Sobel Test. The results show that Green Accounting has a positive and significant effect on profitability, whereas CSRD has no significant effect on profitability. Green Accounting and CSRD do not have a significant effect on firm value, while profitability has a positive and significant effect on firm value. The Sobel Test results indicate that profitability mediates the effect of Green Accounting on firm value but does not mediate the effect of CSRD on firm value. These findings show that the market responds more strongly to financial performance reflected in profitability than to sustainability information disclosed by companies. This study provides empirical evidence of the importance of profitability as a mechanism explaining the relationship between sustainability practices and firm value in the Indonesian energy sector.